MO481KIDNEY FUNCTION MEASURES AND THE RISK OF CANCER INCIDENCE, CANCER DEATH AND ALL-CAUSE MORTALITY*. (29th May 2021) - Lees, Jennifer; Ho, Frederick; Parra-Soto, Solange; Celis-Morales, Carlos; Welsh, Paul; Sullivan, Michael; Jani, Bhautesh; Sattar, Naveed; Pell, Jill; Webster, Angela; Mark, Patrick
Abstract: Background and Aims: Cancer is more common in end-stage kidney disease and in patients on dialysis. We hypothesise that chronic kidney disease (CKD) across the spectrum of disease is associated with increased risk of cancer incidence and cancer death and that this risk is independent of known risk factors for cancer. Furthermore, we assess if risk of cancer incidence (overall and cancer subtypes), cancer death and all-cause mortality is more strongly associated with kidney function-estimating equations incorporating cystatin C. Method: Participants from UK Biobank with baseline measurements of serum creatinine and cystatin C were included, excluding patients with pre-existing cancer. Estimated glomerular filtration rate (eGFR) was calculated using CKD-EPI formulae for creatinine (eGFRcr), cystatin C (eGFRcys) and a combination of creatinine and cystatin C (eGFRcr-cys). Associations of each eGFR with incidence and mortality from overall and specific cancer sites as well as all-cause mortality were tested using Cox proportional hazards models, adjusted for established risk factors for cancer (age, sex, smoking status, alcohol intake, body mass index, ethnicity and deprivation index). Results: .In 443, 441 eligible participants in UK Biobank over median follow-up of 11.3 (IQR 10.6-12.0) years, there were 41, 991 incident cancers, 11, 854 cancer deaths and 23, 708 total deaths. After adjustment for established cancer risk factors and compared to those without significant CKD (eGFR >60 ml/min/1.73m 2 ), CKD G3-5 (eGFR <60 ml/min/1.73m 2 ) was associated with an increased risk of cancer incidence (eGFRcr-cys HR 1.16 (95% CI 1.10 – 1.22); p<0.001), cancer death (eGFRcr-cys HR 1.36 (95% CI 1.25 – 1.48); p<0.001) and all-cause mortality (eGFRcr-cys HR 2.29 (95% CI 2.18-2.41); p<0.001). CKD G3-5 was more strongly associated with risk of cancer incidence, cancer death and all-cause mortality in younger men and women (age <65 years). In particular, younger men and women with CKD G3-5 were more than twice as likely to die from cancer than younger men and women without CKD (eGFRcr-cys HR 2.39 (95% CI 1.99-2.87); p<0.001 and HR 2.12 (95% CI 1.72-2.62); p<0.001 respectively). CKD G3-5 was associated with increased risk of cancer of the abdominal solid organs (eGFRcr-cys HR 1.31 (95% CI 1.07-1.60); p=0.009), respiratory (eGFRcr-cys HR 1.36 (95% CI 1.18-1.56); p<0.001) and renal tracts (eGFRcr-cys HR 1.38 (95% CI 1.18-1.61); p<0.001) and haematological cancers (eGFRcr-cys HR 1.77 (95% CI 1.54-2.03); p<0.001), but was not associated with increased risk of female (breast and reproductive system) or male (prostate, penile and testicular) cancers, cancers of the digestive tract or melanoma (Figure below ). For all outcomes, the strongest associations were found using measures that incorporated cystatin C and were similar for eGFRcys and eGFRcr-cys. Conclusion: These data support routine implementation of cystatin C testing to identify individuals at increased risk of cancer. Younger men and women in particular are increased risk of cancer incidence and cancer death in the context of CKD G3-5. Further exploration is warranted to identify the reasons for worse cancer outcome, particularly in younger patients with CKD.